2019
DOI: 10.1590/1678-5150-pvb-5749
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the mandibular foramen applied to local anesthesia in hoary fox (Lycalopex vetulus)

Abstract: Great part of the veterinary care in wild carnivores is intended to treat the dental disorders, and oral cavity disorders may generally affect the animal health as a whole. It is factual that knowing the location of the mandibular foramen is vital for local anesthetic block of the inferior alveolar nerve, however, there is still no data on the morphometry of the hoary fox mandibular foramen. The aim was describing morphometry of the mandibular foramen of this species and associating its position with anatomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Here, we observed that the mandibular foramen of this species was positioned in the ramus of the mandible, just as Getty (1986) mentioned for swine and other domestic animals, Souza et al (2013) for the crab-eating fox (Cerdocyon thous), and Souza et al (2016) for the maned wolf (Chrysocyon brachyurus). Yet, Magalhães et al (2019) reported that, in the hoary fox (Lycalopex vetulus), the said structure was located in the region of angle of the mandible, while other authors, such as König & Liebich (2016), and Evans & Lahunta (2017) were less specific, as they had, respectively, indicated only the medial face of the mandible with the anatomic reference in domestic animals and in domestic dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we observed that the mandibular foramen of this species was positioned in the ramus of the mandible, just as Getty (1986) mentioned for swine and other domestic animals, Souza et al (2013) for the crab-eating fox (Cerdocyon thous), and Souza et al (2016) for the maned wolf (Chrysocyon brachyurus). Yet, Magalhães et al (2019) reported that, in the hoary fox (Lycalopex vetulus), the said structure was located in the region of angle of the mandible, while other authors, such as König & Liebich (2016), and Evans & Lahunta (2017) were less specific, as they had, respectively, indicated only the medial face of the mandible with the anatomic reference in domestic animals and in domestic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…As far as one can tell, for domestic dogs (Beckman & Legendre, 2002) and cats (Barroso et al, 2009), crab-eating fox (Souza et al, 2013), maned wolf (Souza et al, 2016), and hoary fox (Magalhães et al, 2019), the authors have followed the recommendations of Gross et al (1997) and Egger & Love (2009) to propose the introduction of the needle during the extra-oral technique of the anesthetic block under scrutiny, while using the depression present in the ventral margin of the mandible as a point of reference for the approach of the mandibular foramen. However, in boars, it had been noticed that such osseous accident, addressed by Magalhães et al (2019) as angular incisure, would not be positioned perpendicularly to this foramen, thus leaving it remarkably farther away from the ventral margin of the mandible, which would correlatively increase the space of contact between needle/structure and the risk of local lesions. In addition, in that species, the caudal-ventral-rostral projection of the sulcus for the mylohyoid nerve also renders that form of access unviable, as the nerve would be exposed to the direction of the piercing penetration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mandibular morphometry has been studied in domestic animals such as Saanen goat (Wang et al, 2021), and in wild animals such as crab-eating fox (Souza Junior et al, 2013), maned wolf (Souza Junior et al, 2016), hoary fox (Magalhães et al, 2019), boars (Paulo et al, 2020) and barking deer and sambar deer (Keneisenuo et al, 2021). The morphometric study of the mandible is important because through it one can know the shape and topography of reference sites used in anaesthetic blocking techniques (Souza Junior et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cranial morphometry is crucial for taxonomy and has a major impact on the management and maintenance of the species. Several studies have been conducted regarding the craniometrics of carnivores, including dog (Onar, 1999;Ilgun et al, 2021), wolf (Okarma and Buchalczyk, 1993;Milenković et al, 2010;Khosravi et al, 2012;Gürbüz et al, 2020), fox (Gomes and Valente, 2016;Munkhzull et al, 2018;Magalhães et al, 2019), golden jackal (Monfared, 2013;Rezić et al, 2017) and lynx (Gomerčić et al, 2010;Dayan et al, 2017). Most of these studies include the mandible as the lower part of the facial skeleton.…”
Section: Introductionmentioning
confidence: 99%